Dietary Fiber Hierarchical Specificity: the Missing Link for Predictable and Strong Shifts in Gut Bacterial Communities - Thaisa M. Cantu-Jungles (American Society for Microbiology, 2021)
In the face of interindividual variability and complexity of gut microbial communities, prediction of outcomes from a given fiber utilized by many microbes would require a sophisticated comprehension of all competitive interactions that occur in the gut. Results presented here suggest that high-specificity fibers potentially circumvent the competitive scope in the gut for fiber utilization, providing a promising path to targeted and predictable microbial shifts in different individuals.